Tales and Novels of J. de La Fontaine $1 (BVolume 03s - La Fontaine, Jean de, 1621-1695 (Salt Lake City, UT : Project Gutenberg, 2004)
"Tales and Novels of J. de La Fontaine $1 (BVolume 03" by Jean de La Fontaine is a collection of fables and short stories written during the 17th century, a time often characterized by the Baroque literary movement. This volume features narrative tales that blend humor and moral lessons with themes of love, desire, and societal norms, using animals and humans alike to explore these concepts. The book comprises three distinct tales: "The Muleteer," "The Servant Girl Justified," and "The Three Gossips' Wager." In "The Muleteer," a charming but lowly muleteer finds himself in a precarious situation involving a queen and her king, who unknowingly witnesses the muleteer's amorous escapades. "The Servant Girl Justified" tells of a mischievous affair between a servant and her master's husband, cleverly presented through misunderstandings and jealousies. Lastly, "The Three Gossips' Wager" follows three women who each boast about their husbands, leading to a playful competition filled with deception and comedic twists. Through these entertaining narratives, La Fontaine provides insight into human nature while critiquing social conventions. (This is an automatically generated summary.)s
The Muleteer -- The Servant Girl Justified -- The Three Gossips' Wager.
Release date is 2004-03-01
This eBook was produced by David Widger
Keywords: French poetry -- Translations into English; Fables, French -- Translations into English